1996
DOI: 10.1006/dbio.1996.0167
|View full text |Cite
|
Sign up to set email alerts
|

Induction of Embryonic Vasculogenesis by bFGF and LIFin Vitroandin Vivo

Abstract: The de novo formation of blood vessels (vasculogenesis) is an integral part of embryogenesis. Elucidation of the role of cytokine cooperation in vasculogenesis may lead to a better understanding of organogenesis, blood vessel regulation during tumorigenesis, and tissue injury. We have used embryonic stem cells to derive an endothelial cell line, designated IEM, which expresses a range of endothelial markers, including Von Willibrand Factor VIII related antigen, vascular cell adhesion molecule, platelet-endothe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
31
1

Year Published

2000
2000
2007
2007

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 38 publications
(32 citation statements)
references
References 0 publications
0
31
1
Order By: Relevance
“…VEGFR-1 mediates macrophage chemotaxis (Barleon et al, 1996) and the organization of the embryo vasculature by vasculogenesis (Fong et al, 1995), but not the definitive vessel assembly, which is closely dependent on VEGFR-2, a specific EC differentiation marker (Shalaby et al, 1999). The bFGF/ FGFRs system is mandatory for vasculogenesis, since it induces angioblasts to differentiate and assemble into initial vascular patterns (Gendron et al, 1996).…”
Section: Vasculogenesis In MMmentioning
confidence: 99%
“…VEGFR-1 mediates macrophage chemotaxis (Barleon et al, 1996) and the organization of the embryo vasculature by vasculogenesis (Fong et al, 1995), but not the definitive vessel assembly, which is closely dependent on VEGFR-2, a specific EC differentiation marker (Shalaby et al, 1999). The bFGF/ FGFRs system is mandatory for vasculogenesis, since it induces angioblasts to differentiate and assemble into initial vascular patterns (Gendron et al, 1996).…”
Section: Vasculogenesis In MMmentioning
confidence: 99%
“…It has been shown to cause proliferation (Gendron et al, 1996) and induce tube-formation (Paradis and Gendron, 2000) of an embryonic endothelial cell line. However, it had differential effects on bovine endothelial cells depending on the tissue origin of the cells.…”
Section: Introductionmentioning
confidence: 99%
“…Although factors such as VEGF, which modulates cornea, and new vascularisation has been characterised, the process of vascularisation is far from clear. Several studies have indicated that LIF could play a role in the regulation of blood vessel formation, [25][26][27][28][29] and LIF may have an implication in pathological vascularisation in ocular tissues. Depending upon the tissue origin or stage of differentiation, LIF has been shown to exert different actions.…”
Section: Discussionmentioning
confidence: 99%
“…LIF stimulates adrenal cortex endothelial cells and embryonic cells, while it inhibit aortic endothelial cells. [25][26][27] Embryonic endothelial cell line can be optimally induced to differentiate into capillary-like structures in vitro by combined exposure to LIF plus bFGF. 26,28 During the formation of capillary structures from embryonic endothelial cell, line twoFStat3 and P 41/43MAPK cascade systems are activated.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation